Matrix bound nanovesicle-associated IL-33 activates a pro-remodeling macrophage phenotype via a non-canonical, ST2-independent pathway - Hussey, George S. (J Immunol Regen Med, 2019)
The regenerative healing response of injured skeletal muscle is dependent upon an appropriately timed switch from a local type-I to a type-II immune response. Biologic scaffolds derived from extracellular matrix (ECM) have been shown to facilitate a macrophage phenotype transition that leads to downstream site-appropriate functional tissue deposition and myogenesis. However, the mechanisms by which ECM directs the switching of immune cell phenotype are only partially understood. Herein, we provide the first evidence that matrix bound nanovesicles (MBV) embedded within ECM-scaffolds are a rich and stable source of interleukin-33 (IL-33), an alarmin/cytokine with emerging reparative properties. We show that IL-33 encapsulated within MBV bypass the classical IL33/ST2 receptor signaling pathway to direct macrophage differentiation into the reparative, pro-remodeling M2 phenotype, which in turn facilitates myogenesis of skeletal muscle progenitor cells. Our results suggest the potential of IL-33(+) MBV as a clinical therapy to augment the restorative efficacy of existing ECM-based and non-ECM based approaches.